Philippine agenda - Soho, Jessica; Clavio, Arnold; Enriquez, Mike.; Tiangco, Mel.; Morales, Vicky; Parungao, Monti; GMA Networks, Inc. (Quezon City GMA Network, 2007)
This groundbreaking pre-election series combined the efforts of GMA Network's multi-awarded news and public affairs teams to present the country's biggest issues with the objective of calling viewers to action.
Edukasyon ni Jessica Soho (32 min.) -- Kalusugan ni Arnold Clavio (31 min.) -- Katiwalian ni Mike Enriquez (33 min.) -- Pabahay ni Mel Tiangco (30 min.) -- Trabaho ni Vicky Morales (35 min.) -- Gutom ni Mike Enriquez (32 min.) -- Krimen at hustisya ni Arnold Clavio (33 min.) -- Reporma sa eleksyon ni Jessica Soho (29 min.).
Summary from cover.
VP-public affairs, Nessa S. Valdellon ; Associate producer and production coordinator, Annabelle Sunpongco ; Theme music by Ditoy Aguila ; Executive producers, Joy Madrigal, Angeli Guidaya, Sherilyn Bruan and Lee Joseph Castel ; Directors, Monti Parungao ... [et al.].
Hosts, Jessica Soho, Arnold Clavio, Mike Enriquez, Mel Tiangco and Vicky Morales.
DVD.
Keywords: Education -- Philippines; Health Services Needs and Demand -- Philippines; Political corruption -- Philippines -- Prevention; Housing -- Philippines; Labor supply -- Philippines; Hunger -- Philippines; Crime -- Philippines; Election reform -- Philippines; Elections -- Philippines -- 2007.; Philippines -- Social conditions; Philippines -- Politics and government -- 2007-.